2008
DOI: 10.1055/s-0028-1088332
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Attenuates High-Fat-Diet-Induced Atherosclerosis in Rabbits by Anti-Inflammatory Activity

Abstract: Cortex Moutan (Paeonia suffruticosa Andrews, Ranunculaceae) has several uses in traditional medicine, such as analgesic, antipyretic, and anti-inflammatory applications and use in the prevention of thromboembolic diseases. Paeonol, a main active component in Cortex Moutan, possesses various pharmacological activities, particularly an anti-atherosclerosis effect. However, so far there have been no reports evaluating the anti-inflammatory action of paeonol in atherosclerosis therapy. The purpose of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 20 publications
1
56
0
Order By: Relevance
“…Paeonol is used as a food additive and in traditional oriental medicines in treating various diseases including inflammatory diseases and atherosclerosis [7]. Recent studies have also revealed that paeonol attenuates high-fat-diet-induced atherosclerosis in rabbits [8] and inhibits RANKL-induced osteoclastogenesis [9]. Accordingly, paeonol may be a potential therapeutic agent for treating inflammation-associated conditions, such as inflammatory pain.…”
Section: Introductionmentioning
confidence: 98%
“…Paeonol is used as a food additive and in traditional oriental medicines in treating various diseases including inflammatory diseases and atherosclerosis [7]. Recent studies have also revealed that paeonol attenuates high-fat-diet-induced atherosclerosis in rabbits [8] and inhibits RANKL-induced osteoclastogenesis [9]. Accordingly, paeonol may be a potential therapeutic agent for treating inflammation-associated conditions, such as inflammatory pain.…”
Section: Introductionmentioning
confidence: 98%
“…SIRT1 activation by RSV improves vascular function by increasing NO availability and attenuates dyslipidemia and obesity-induced metabolic alterations in human subjects (44)(45)(46). Paeonol can alleviate the oxidative stress-related cardiovascular diseases predominantly through the modulation of endogenous antioxidants and reduction of free radical formation (47,48).Two different endothelial cell types-ECFCs and HUVECs-were used in this study. They are the first vascular cells of the fetus that are exposed to aberrant conditions and an adverse metabolic milieu during pregnancy.…”
mentioning
confidence: 99%
“…In response to fat and cholesterol feeding, rabbits develop the most well-established MetS features, including systemic inflammation, glucose intolerance, hyperlipidemia, hypertension, accrual of visceral fat tissue, and fatty liver disease [25]- [32]. Relative to mice, the lipoprotein profile of rabbits also corresponds more closely to humans, and in contrast to mice, which exhibit an atheroprotective phenotype, rabbits with a constellation of MetS features develop coronary atherosclerotic lesions resembling that of humans [24] [26]. In addition, as rabbits exhibit a longer life span of 5 -8 years, lengthier study durations may afford more extensive interrogation of MetS and its complications in an easily handled, inexpensive animal model.…”
Section: Discussionmentioning
confidence: 99%